2007
DOI: 10.1136/bjsm.2007.043943
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exercise intensity on lymphocyte H2O2production and antioxidant defences in soccer players

Abstract: Exercise intensity affects the lymphocyte and neutrophil oxidant/antioxidant balance, but only exercise of high intensity induces lymphocyte oxidative damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
53
0
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 42 publications
5
53
0
7
Order By: Relevance
“…Cordyceps sinensis scavenges ROS, superoxide anions and hydroxyl radicals by inhibiting malondialdehyde formation (30). In high intensity or exhaustive exercise, the overproduction of ROS is observed (31). Supporting endogenous antioxidant systems with additional oral antioxidants has been demonstrated to prevent or reduce oxidative stress, decrease muscle damage and improve exercise performance (32).…”
Section: Discussionmentioning
confidence: 99%
“…Cordyceps sinensis scavenges ROS, superoxide anions and hydroxyl radicals by inhibiting malondialdehyde formation (30). In high intensity or exhaustive exercise, the overproduction of ROS is observed (31). Supporting endogenous antioxidant systems with additional oral antioxidants has been demonstrated to prevent or reduce oxidative stress, decrease muscle damage and improve exercise performance (32).…”
Section: Discussionmentioning
confidence: 99%
“…There are several studies which indicate that an increase in free radical production especially in active skeletal muscles. [12][13][14] Sureda et al [15] found an increased Malondialdehyde due to oxidative stress in lymphocytes after a single bout of intense exercise. Similarly Ajmani et al [16] noted increased membrane rigidity in erythrocytes after strenuous exercise because of oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…However, intense physical exercise can increase oxygen consumption by up to 10-to 20-fold over resting levels to meet energy demands, and oxygen uptake in active skeletal muscle increase 100-to 200-fold (Sureda et al, 2009). Increased oxygen uptake during exercise is accompanied by an elevation in reactive oxygen species (ROS), and ROS are harmful to cells, mainly because they injure lipids, proteins and nucleic acids, which leads to structural and functional impairments (Duthie et al, 1990;Mantle and Preedy, 1999;Alessio et al, 2000;Jackson, 2005).…”
Section: Introductionmentioning
confidence: 99%